The DEEP Groth Strip Galaxy Redshift Survey. III. Redshift Catalog and Properties of Galaxies - Weiner, Benjamin J; Phillips, Andrew C; Faber, S. M; Willmer, Christopher N. A; Vogt, Nicole P; Simard, Luc; Gebhardt, Karl; Im, Myungshin; Koo, D. C; Sarajedini, Vicki L; Wu, Katherine L; Forbes, Duncan A; et al. (The Astrophysical journal, 2005)
The Deep Extragalactic Evolutionary Probe (DEEP) is a series of spectroscopic surveys of faint galaxies, targeted at understanding the properties and clustering of galaxies at redshifts z similar to 1. We present the redshift catalog of the DEEP1 Groth Strip pilot phase of this project, a Keck LRIS survey of faint galaxies in the Groth Survey Strip imaged with HST WFPC2. The redshift catalog and data, including reduced spectra, are made publicly available through a Web-accessible database. The catalog contains 658 secure galaxy redshifts with a median z = 0.65. The distribution of these galaxies shows large-scale structure walls to z similar to 1. We find a bimodal distribution in the galaxy color-magnitude diagram that persists to the same distance. A similar color division has been seen locally by the SDSS and to z similar to 1 by the COMBO-17 survey. The HST imaging allows us to measure structural properties of the galaxies, and we find that the color division corresponds generally to a structural division. Most red galaxies, similar to 75%, are centrally concentrated, with a red bulge or spheroidal stellar component, while blue galaxies usually have exponential profiles. However, there are two subclasses of red galaxies that are not bulge dominated: edge-on disks and a second category that we term diffuse red galaxies (DIFRGs). Comparison to a local sample drawn from the RC3 suggests that distant edge-on disks are similar in appearance and frequency to those at low redshift, but analogs of DIFRGs are rare among local red galaxies. DIFRGs have significant emission lines, indicating that they are reddened mainly by dust rather than age. The DIFRGs in our sample are all at z > 0.64, suggesting that DIFRGs are more prevalent at high redshifts; they may be related to the dusty or irregular extremely red objects beyond z > 1.2 that have been found in deep K-selected surveys. We measure the color evolution of both red and blue galaxies by comparing our U - B colors to those from the RC3. For red galaxies, we find a reddening of only 0.11 mag from z similar to 0.8 to now, about half the color evolution measured by COMBO-17. Larger, more carefully defined samples with better colors are needed to improve this measurement. Reconciling evolution in color, luminosity, mass, morphology, and star formation rates will be an active topic of future research.